2000
DOI: 10.1006/jmre.1999.1990
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Quadrupolar and Magnetic Contributions to Spin–Lattice Relaxation in the Case of a Single Isotope

Abstract: We present a NMR pulse double-irradiation method which allows one to separate magnetic from quadrupolar contributions in the spin-lattice relaxation. The pulse sequence fully saturates one transition while another is observed. In the presence of a |∆m| = 2 quadrupolar contribution, the intensity of the observed line is altered compared to a standard spin-echo experiment. We calculated analytically this intensity change for spins I = 1, 3/2, 5/2, thus providing a quantitative analysis of the experimental result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Phonons will cause nuclear relaxation for quadrupolar nuclei (I > 1/2, like Cu and O) as they modulate the electric field gradient, but it has been shown that the magnetic fluctuations dominate in most situations [ 20,21], and the recent analysis of all Cu relaxation data shows that a simple magnetic mechanism appears to capture the overall behavior quite well [16,17].…”
Section: Planar Cu Relaxationmentioning
confidence: 99%
“…Phonons will cause nuclear relaxation for quadrupolar nuclei (I > 1/2, like Cu and O) as they modulate the electric field gradient, but it has been shown that the magnetic fluctuations dominate in most situations [ 20,21], and the recent analysis of all Cu relaxation data shows that a simple magnetic mechanism appears to capture the overall behavior quite well [16,17].…”
Section: Planar Cu Relaxationmentioning
confidence: 99%
“…Thus, for a static field H 0 [001] HTT , the quantity 63 (T 1 T ) −1 reflects the weighted q average of χ"(q, ω 0 ), the imaginary part of the in-plane dynamical spin susceptibility at the frequency ω 0 . The magnetization recovery curves for 63 Cu were therefore fitted to the standard expression [20] for a purely magnetic relaxation over the entire temperature range investigated assuming a single T 1 . The temperature dependence of 63 (T 1 T ) −1 is shown in Fig.…”
mentioning
confidence: 99%
“…When T 1Q1 is only slightly larger than T 1Q2 (4 s vs. 3 s) the calculated recovery curve appears to be reasonably close to single-exponential; forcing a fit of this curve to a single-exponential gives a time constant T 1 ("T 1Q1 = T 1Q2 ) = 2.2 s. The expanded difference plot shows that the calculated recovery curve agrees within a couple of percent of that for a single-exponential; however, the corresponding time constants are substantially different, with T 1Q1 , T 1Q2 > T 1 . These simulations clearly demonstrate that even though experimental relaxation curves may closely approximate single-exponential recovery, Table 1 Experimental conditions for saturation-recovery measurements (see Ga, magic-angle (0) 6 Not achievable (0) 6 (5.4) n a 90°pulse for CT = 12.5 ls. b CT inadvertently excluded from list; nevertheless, CT saturation measured to be 89% of full saturation, with negligible calculated effects on recovery curves.…”
Section: General Strategymentioning
confidence: 95%
“…The description of spin-lattice relaxation in multilevel systems of half-integral quadrupolar nuclei dates back a half century to Pound's original work [1]. Subsequent studies have emphasized solutions to the set of coupled rate equations describing the populations of each level [2][3][4][5][6]. These solutions depend upon both the initial state of the spin system in a given T 1 experiment, as well as the nature of the relaxation mechanism (viz., whether quadrupolar or magnetic in nature).…”
Section: Introductionmentioning
confidence: 99%